Tuning a UV-C device to challenge new threats in the sanitization setting of healthcare facilities. (30th September 2020) - Amodeo, D; Pallecchi, L; Nagaia, C; Spataro, G; Cardaci, R; Messina, G
Abstract: Background: Environmental hospital hygiene plays a role in healthcare-associated infections emergency caused by resistant multi-drug organisms. The implementation of new and effective disinfection procedures is now more than ever important to prevent the cross-transmission of pathogens in the hospital facilities. In combination with common chemicals biocides, UV technology is a realistic option for environmental disinfection. In this study, we evaluate a UV device for its effectiveness on an emerging pathogen. Methods: A laboratory cross section experiment was performed between August and October 2019. Two different strains of Candida auris (CBS 10913 and CBS 12372) were tested on 20 cm2 stainless steel carriers inoculated with 10 µl of bacterial culture at a concentration of 1x105 CFU/mL. The inoculum was spread until dry in aseptic condition. Carriers were placed parallel to the UV device, having 4 UV-C lamps that emit 325 W, at a fixed distance of 2.44 m. Biocidal tests were carried out in triple at three different light exposure times (5, 10 and 20 minutes). After treatment, laboratories procedures were used to detach and transfer the remaining microorganisms from the carriers to plates and compared them to controls after incubation at 37 °C for 48 h. Results: A significant inactivation of C. auris already occurred at 5 minutes, reaching 3-4 log10 reduction at 20 minutes of UV-C exposure. No substantial differences were identified by analyzing the results between the two strains. Conclusions: The chosen distance of 2.44 m from the target allows to ideally sanitize an entire hospital room. However, to avoid the limit of shaded areas due to the presence of non-movable objects, a couple of positions are recommended, so that shorter distances can reduce the exposure time or increase the average irradiance level of exposed surfaces. Key messages: In sanitation of hospital environments, the use of viable alternatives as UV-C can contribute to the reduction of infections caused by multidrug-resistant microorganisms. Accurate testing of different space-time irradiation configurations allows to achieve important results related to the biocidal effects of UV devices.